Hybrid ceramic membranes for water electrolysis applications
Gas spanning and mechanical stability in alkaline water electrolysis applications by using TiO2 nanoparticles and metal oxide nanoparticles with polymer resin in ceramic membranes and by coating and polymer filling holes, the gas span and mechanical stability of ceramic membranes in alkaline water electrolysis applications is solved. The problem of insufficient properties has achieved high chemical thermal stability and low gas spanning effect of dense composite polymer-ceramic membranes.
Patent Information
- Application Number
- CN202380048570.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-22
- Filing Date
- 2023-06-19
- Publication Date
- 2025-02-07
AI Technical Summary
In the application of alkaline water electrolysis, existing ceramic membranes have gas spanning problems and insufficient mechanical stability, making it difficult to achieve densification and high chemical thermal stability.
The ceramic porous support layer was prepared by combining TiO2 nanoparticles and other metal oxide nanoparticles with curable polymer resin, and the holes were coated with TiO2 suspension and polymer-filled to form a dense composite polymer-ceramic membrane.
It realizes densification of ceramic membranes, reduces gas span, improves mechanical strength and chemical thermal stability, and is suitable for alkaline water electrolysis and related electrochemical applications.
Smart Images

Figure BDA0005199355330000161 
Figure BDA0005199355330000181 
Figure HDA0005199355350000011
Abstract
Description
Technical Field
[0001] The present invention relates to a dense composite polymer-ceramic membrane and a method of making the same. In particular, the membrane comprises a porous ceramic support layer, coated with a nanoparticle layer and the pores are filled with an ion-conducting polymer for use in alkaline water electrolysis applications. Background Art
[0002] Ceramic membranes are known to be used in various applications such as liquid filtration, gas separation and energy devices due to their good mechanical strength and stability against chemical attack. They can withstand harsh conditions such as high pH, low pH, high temperature and high pressure, etc. On the other hand, porous polymer membranes cannot withstand such harsh conditions, although they are easy to process and prepare.
[0003] Hydrogen is used in almost every industry, including the stationary and transportation markets, petroleum refining and fertilizer production as an energy carrier. Currently, hydrogen is primarily derived from fossil fuels (mainly natural gas as well as heavy oil and naphtha) via steam hydrocarbon (e.g. methane) reforming, where hydrocarbons (e.g. methane) react with steam in the presence of a catalyst to produce hydrogen and carbon dioxide (CO2). This raises environmental concerns, as emitted CO2 is a major contributor to global climate change.
[0004] Another way is to produce hydrogen from water using renewable energy, which has become particularly attractive and is considered the most promising technology because it only emits water and oxygen as byproducts and no CO2 emissions. Hydrogen produced in this way is called green hydrogen because water is split into only oxygen and hydrogen under the action of electricity.
[0005] In alkaline water electrolysis using aqueous KOH or NaOH as the electrolyte, water is first reduced to hydroxide ions (OH - ) and hydrogen (2H2O+2e - →H2+2OH - ). The generated OH - The ions then migrate across the membrane to the anode and release O2 and water
[0006] The two electrodes are separated by a membrane. The main function of the membrane is to provide OH - Ion conduction and avoidance of gaseous product crossover. It also prevents electrolyte mixing and short circuiting. For the reasons stated, the separator membrane should be dense but have low resistance to transmembrane ion migration.
[0007] Currently, commercially available Zirfon TMPerl UTP 500 (Agfa-Gevaert NV), a 500 μm thick porous composite made of zirconium dioxide (ZrO2) and polysulfone, is the most commonly used membrane in alkaline water electrolysis (10.1149 / 1945-7111 / abda57).
[0008] When this porous membrane is used, H2 gas can diffuse into the O2 stream and cause an explosion when the H2 concentration reaches the lower explosion limit (4%). In addition, according to the manufacturer's data sheet, Zirfon TM The maximum operating temperature of Perl UTP 500 is only 110℃.
[0009] Therefore, a scalable method to prepare free-standing mechanically robust hybrid ceramic membranes with controlled pore size remains elusive.
[0010] On the other hand, despite recent progress in the development of anion exchange membranes (AEMs), durable and optimized AEMs for alkaline water electrolysis cells remain to be developed (https: / / doi.org / 10.1115 / 1.4047963).
[0011] Known porous ceramic membranes include a thick porous support layer that provides mechanical strength and one or more thin selective inorganic (and / or polymer) layers. They are usually prepared using metal oxides (mainly Al2O3, TiO2, SiO2 or ZrO2 powders, etc.) or their combinations.
[0012] Campbell (US2019 / 0389778 A1) discloses a method for preparing a 3D porous ceramic material for a carbon dioxide capture system. It is reported that the pores are connected from one side of the ceramic structure through the ceramic structure to the opposite side of the material.
[0013] These films exhibit excellent mechanical and chemical stability properties.
[0014] However, there is a need to further densify (narrow the pore size) membranes for alkaline water electrolysis. One way is to fill / densify the pores of ceramic membranes by coating the membrane with a layer of nanoparticles.
[0015] Growing polymer brushes on ceramic materials is another attractive approach that has recently been used to functionalize and densify porous ceramic membranes for nanofiltration membrane processes (PCT patent publication WO2020016068).
[0016] Therefore, it would be desirable to develop durable hybrid ceramic membranes with high chemical and thermal stability and no / low (H2) gas crossover for alkaline water electrolysis and / or related systems by first making porous ceramic membranes and further densifying via nanoparticles and ion-conducting polymer materials. Summary of the invention
[0017] Thus, according to a first aspect of the present invention, there is provided a method of preparing a dense hybrid ceramic membrane (hereinafter also referred to as a dense composite polymer-ceramic material) as set out in the accompanying claims.
[0018] The method of making such a dense composite polymer-ceramic material as defined in the appended claims comprises:
[0019] combining TiO2 nanoparticles, at least another metal oxide nanoparticles, and a curable polymer resin to produce a mixture;
[0020] curing the mixture to obtain a first composite material;
[0021] heating the first composite material to a first temperature to remove the polymer from the first composite material to obtain a second composite material;
[0022] heating the second composite material to a second temperature to sinter the TiO2 nanoparticles and the at least one additional metal oxide nanoparticles, thereby producing a ceramic porous support layer;
[0023] coating the ceramic porous support layer with a TiO2 suspension to obtain a ceramic porous support layer coated with TiO2; and
[0024] • Filling the pores of the TiO2 coated ceramic porous support layer with a polymer to obtain a dense composite polymer-ceramic material as defined in any of the appended claims.
[0025] In an embodiment of the method according to the present invention, at least the additional metal oxide nanoparticles are selected from aluminum oxide (Al2O3), yttria fully stabilized zirconia (Y2O3-doped ZrO2 (YSZ)), yttria tetragonal zirconia polycrystalline (Y2O3-doped ZrO2 (Y-TZP)), CeO2, CeO2 tetragonal ZrO2 polycrystalline (Ce-TZP), ZrO2, SiO2, SnO2 and the like; in particular, at least the additional metal oxide nanoparticles are yttria-doped zirconium oxide (YSZ).
[0026] In an embodiment of the method according to the present invention, the mixture of TiO2 nanoparticles, at least additional metal oxide nanoparticles and a curable polymer resin comprises about 1 wt% to about 20 wt% of the total mixture, specifically about 5 wt% to about 15 wt% of the total mixture of TiO2 nanoparticles.
[0027] In an embodiment of the method according to the present invention, the mixture of TiO2 nanoparticles, at least additional metal oxide nanoparticles and a curable polymer resin contains about 50 wt% to about 80 wt% of the total mixture, specifically about 60 wt% to about 70 wt% of the total mixture of at least additional metal oxide nanoparticles.
[0028] In an embodiment of the method according to the invention, the TiO2 suspension comprises about 1 wt% to about 5 wt% TiO2.
[0029] In an embodiment of the method according to the invention, the ceramic porous support layer is coated with TiO2 via dip coating.
[0030] In the method of making a dense composite polymer-ceramic material as defined in the accompanying claims, the porous ceramic support layer coated with TiO2 is further functionalized by filling the pores of the porous ceramic support layer coated with TiO2 with a polymer.
[0031] As mentioned above, in the method of the present invention, the polymer filling of the pores can be carried out via polymer impregnation or in situ polymerization of the pore walls. The in situ polymerization can, for example, consist of a surface initiated atom transfer radical polymerization (SI-ATRP) reaction; in particular, monomers such as (but not limited to) acrylates and styrene derivatives are used. The polymer impregnation can be accomplished using any suitable polymer, such as polysulfone (PSU) and poly-p-phenylene oxide (PPO), anion binding polymers, ionomers, or combinations thereof.
[0032] In the embodiment wherein polymer impregnation is accomplished using an ionomer, the ionomer is specifically selected from a halogen ionomer, such as a fluorinated ionomer containing sulfonate groups based on ionized sulfonic acid (e.g., fluorosulfonic acid (i.e., FSA) ionomer); or a hydrocarbon ionomer, which preferably contains (meth)acrylate groups based on ionized (meth)acrylic acid; or a combination thereof.
[0033] In a specific embodiment, the present invention provides a method for manufacturing a bipolar membrane using a ceramic porous support layer or a porous ceramic support layer coated with TiO2 as provided herein, and characterized in that:
[0034] Filling the pores of one side of either ceramic porous layer with a first ionomer via diffusion of a solution of the ionomer from that side followed by precipitation of the ionomer, and
[0035] • Filling the pores of the other side of either ceramic porous layer with a second ionomer via diffusion of a solution of the ionomer from the second side followed by precipitation of the ionomer.
[0036] In another embodiment, the present invention provides a method for making a bipolar membrane using a ceramic porous support layer coated with TiO2 as provided herein, and characterized in that:
[0037] Filling the pores of one side of a ceramic porous support layer coated with TiO2 with a first ionomer via diffusion of a solution of the ionomer from that side followed by precipitation of the ionomer, and
[0038] • Filling the pores of the other side of the TiO2 coated ceramic porous support layer with a second ionomer via diffusion of a solution of the ionomer from the second side followed by precipitation of the ionomer.
[0039] According to a second aspect, the present invention provides a dense composite polymer-ceramic material comprising:
[0040] a. a ceramic porous support layer consisting of TiO2 nanoparticles and at least another metal oxide nanoparticles,
[0041] b. a porous coating of TiO2 nanoparticles coated on the ceramic porous support layer, and
[0042] c. A polymer that fills at least the pores of the ceramic porous material.
[0043] In an embodiment of the dense composite polymer-ceramic material according to the present invention, the polymer filler is present in the pores of the ceramic porous support layer and in the pores of the porous coating of the TiO2 nanoparticles.
[0044] In an embodiment of the dense composite polymer-ceramic material according to the present invention, at least additional metal oxide nanoparticles are selected from alumina (Al2O3), yttria fully stabilized zirconia (Y2O3-doped ZrO2 (YSZ)), yttria tetragonal zirconia polycrystalline (Y2O3-doped ZrO2 (Y-TZP)), CeO2, CeO2 tetragonal ZrO2 polycrystalline (Ce-TZP), ZrO2, SiO2, SnO2 and the like; specifically, at least additional metal oxide nanoparticles are yttria-doped zirconia (YSZ).
[0045] It is evident from the manufacturing method mentioned above that a mixture of a polymer resin comprising TiO2 nanoparticles and at least another metal oxide nanoparticles is used in the material preparation. Therefore, it is not surprising that some polymer resin may be present in the porous ceramic support layer obtained after curing and sintering. Therefore, in an embodiment of the dense composite polymer-ceramic material according to the present invention, it also comprises a polymer resin, in particular a crosslinkable polymer.
[0046] In an embodiment of the dense composite polymer-ceramic material according to the present invention, the polymer resin is selected from acrylates that can be cross-linked using a thermal initiator (e.g., a cross-linking agent), or acrylates that can be cross-linked using an initiator activated by ultraviolet (UV) light, such as but not limited to polyethylene glycol diacrylate (PEGDA) plus a thermal initiator (e.g., 3 wt. % Luperox 331).
[0047] In an embodiment of the dense composite polymer-ceramic material according to the present invention, the porous ceramic support layer comprises TiO2 nanoparticles in an amount of about 1 wt% to about 20 wt% of the total porous ceramic support layer, specifically about 5 wt% to about 15 wt% of the total porous ceramic support layer.
[0048] In an embodiment of the dense composite polymer-ceramic material according to the present invention, the ceramic porous support layer, also referred to herein as a porous ceramic support material, comprises at least additional metal oxide nanoparticles in an amount of about 50 wt % to about 80 wt % of the total porous ceramic support material, specifically about 60 wt % to about 70 wt % of the total porous ceramic support material.
[0049] In an embodiment of the dense composite polymer-ceramic material according to the present invention, the ceramic porous support layer has an average pore size of about 80 to 200 nm.
[0050] In an embodiment of the dense composite polymer-ceramic material according to the present invention, the ceramic porous support layer is a membrane having a thickness of about 50 to 2000 μm, specifically 50 to 1000 μm, more specifically 50 to 200 μm.
[0051] In an embodiment of the dense composite polymer-ceramic material according to the present invention, the coating of TiO2 nanoparticles has an average thickness of 0.5 to 5 μm and an average pore size distribution of 50 to 150 nm.
[0052] In an embodiment of the dense composite polymer-ceramic material according to the present invention, filling the pores of at least the ceramic porous support layer with a polymer is accomplished via polymer impregnation, wherein the polymer is selected from any suitable polymer, such as polysulfone (PSU) and polyparaphenylene ether (PPO), anion binding polymers, ionomers or combinations thereof.
[0053] In an embodiment of the dense composite polymer-ceramic material according to the present invention, filling the pores of at least the ceramic porous support layer with a polymer is accomplished using an ionomer selected from: a halogen ionomer, such as a fluorinated ionomer containing sulfonate groups based on ionized sulfonic acids (e.g., fluorosulfonic acid (i.e., FSA) ionomers); or a hydrocarbon ionomer, which preferably contains (meth)acrylate groups based on ionized (meth)acrylic acid; or a combination thereof.
[0054] In an embodiment of the dense composite polymer-ceramic material according to the present invention, filling the pores of at least the ceramic porous support layer with a polymer is accomplished using in situ polymerization of the pore walls, specifically using a surface initiated atom transfer radical polymerization (SI-ATRP) reaction, more specifically using SI-ATRP of monomers such as (but not limited to) acrylates and styrene derivatives.
[0055] In a third aspect, the present invention provides the use of a dense composite polymer-ceramic material as defined herein or obtained according to a process of the invention in filtration or electrochemical applications such as fuel cells, hydrogen peroxide production and alkaline water electrolysis.
[0056] In a specific embodiment, the porous ceramic support layer is made of 3 mol% yttria-stabilized zirconia (referred to herein as YSZ) and TiO2 nanoparticles. Advantageously, the TiO2 nanoparticles improve the mechanical stability of the membrane. In addition, the dimensional shrinkage and bending after sintering are improved.
[0057] In the following step, a thin coating of TiO2 particles is deposited on top of the exemplary porous ceramic support material to change the pore size and pore size distribution of the membrane. Advantageously, this fills the surface macropores, narrows the pore size distribution, and improves the mechanical strength of the prepared membrane.
[0058] Finally, the examples below provide three possible modes for further densifying the pores of the thus obtained porous ceramic support material coated with TiO2 using polymers such as anion exchange polymers as pore fillers: (i) the porous ceramic support material is functionalized to accommodate polymerization initiated from the pore walls, (ii) a monomer solution of a targeted ion exchange polymer diffuses through the pores and subsequently initiates polymerization until the pores are completely filled, or iii) a polymer and / or ionomer solution diffuses through the pores, followed by polymer / ionomer precipitation via phase inversion or solvent evaporation.
[0059] In all cases, the ceramic material can be additionally (pre- or post-)functionalized to further accommodate OH - Ion-conducting groups. After polymerization of the pores, the material will behave as a dense hybrid membrane (Meynen V. et al., Current Organic Chemistry, 18:18, 2014, 2334-2350), which significantly reduces gas crossover while maintaining its ion-conducting properties due to the properties of the AEM polymer / functionalized ceramic used (Christopher G. Arges and Le Zhang, ACS Appl. Energy Mater., 2018, 1, 7, 2991-3012).
[0060] Membranes with different densification degrees (and / or different pore sizes) can be obtained using the method of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0061] Various aspects of the invention will now be discussed in more detail with reference to the drawings, wherein like reference numerals indicate like attributes.
[0062] Figure 1 is the viscosity of YSZ-TiO2 slurry at 25℃.
[0063] Figure 2 is the percentage of polymer removed after membrane sintering of the membrane according to the invention.
[0064] Figure 3 The pore size distribution of the ceramic porous support layer used in the manufacture of the dense composite polymer-ceramic membrane according to the present invention is shown.
[0065] Figure 4 The thermal stability of the ceramic porous support material according to the present invention is shown.
[0066] Figure 5 This is a preliminary alkaline water electrolysis test using the prepared porous ceramic membrane (YSZ-TiO2) and the porous ceramic membrane coated with TiO2 (YSZ-TiO2-T) (700um).
[0067] Figure 6 A flow chart of a dense composite polymer-ceramic membrane preparation process according to the method of the present invention is shown.
[0068] Description of the implementation plan
[0069] A list of abbreviations used in the specification is provided below.
[0070] AEM Anion Exchange Membrane
[0071] CO2 Carbon dioxide
[0072] ℃ Celsius
[0073] DI water
[0074] DMF N,N-Dimethylformamide
[0075] g
[0076] He Helium
[0077] Hg Mercury
[0078] H Hour
[0079] H2 Hydrogen
[0080] H2O water
[0081] KOH Potassium Hydroxide
[0082] L331 331M80, 1,1-bis(tert-butylperoxy)cyclohexane solution
[0083] mg milligram
[0084] mL milliliters
[0085] min
[0086] nm nanometer
[0087] NMP N-Methyl-2-pyrrolidone
[0088] OH - Hydroxide ion
[0089] O2 Oxygen
[0090] PEGDA Polyethylene glycol diacrylate
[0091] PVA Polyvinyl Alcohol
[0092] rpm revolutions per minute
[0093] RO Reverse Osmosis
[0094] RT Room temperature
[0095] SEM Scanning Electron Microscope
[0096] SI-ATRP Surface-Initiated Atom Transfer Radical Polymerization
[0097] S seconds
[0098] TiO2 Titanium Oxide
[0099] TGA Thermogravimetric Analysis
[0100] μm micrometer
[0101] Wt.% Weight percentage
[0102] YSZ 3mol% yttria stabilized zirconia
[0103] YSZ-TiO2 Film made of YSZ and TiO2
[0104] YSZ-TiO2-T YSZ-TiO2 film coated with TiO2 nanoparticles
[0105] YSZ-TiO2-T-ionomer YSZ-TiO2-T membrane modified with ionomer
[0106] ZrO2 Zirconium Oxide
[0107] As mentioned above, the object of the present invention is to provide materials for alkaline water electrolysis applications, in particular dense composite polymer-ceramic membranes, which comprise a porous ceramic support, coated with a layer of TiO2 nanoparticles and the pores are filled with an ion-conducting polymer. It has been found that for water electrolysis applications, the use of such a combination of coating of TiO2 nanoparticles and polymer filling of the pores can prevent gas crossover without affecting anionic conductivity.
[0108] As used herein, 'dense' composite polymer-ceramic membrane means a 'dense' membrane of a polymer-ceramic material, wherein such a 'dense' membrane consists of a structure with no detectable pores at the limit of electron microscopy (typically with a lower limit of about 0.1 nm, including pores with an average pore size of up to 0.1 nm), but which still allows molecules to be transported across the membrane by diffusion under the driving force of pressure, concentration or potential gradients.
[0109] To the extent described, it has been found to be beneficial to combine TiO2 nanoparticles with at least another metal oxide nanoparticle, preferably yttrium-doped zirconium oxide (YSZ) and a curable polymer resin, preferably a curable cross-linkable polymer such as polyethylene glycol diacrylate (PEGDA), in the production of a porous ceramic support layer. In the absence of TiO2, casting of the material is possible, but the porous ceramic support layer thus obtained is visibly warped / deformed (not flat). The addition of TiO2 nanoparticles (in particular at least 10% by weight) solves this problem.
[0110] Thus, in a first step of manufacturing the material according to the invention, this mixture of TiO2 nanoparticles with at least another metal oxide nanoparticles and a curable polymer resin is shaped, for example by (but not limited to) mold casting, rotational casting or knife casting, and subsequently cured by initiating the curable polymer resin, resulting in a so-called green body of the final product (see Examples 1 and 2 below).
[0111] In a subsequent step, the green body is sintered to densify and solidify the metal oxide and TiO2 nanoparticles while at least partially removing the polymer resin, thereby obtaining a porous ceramic support layer (see Example 3). Although the material thus obtained has a surprisingly narrow pore size distribution (see Figure 3), but the average pore size of this material cannot be used in an electrochemical cell, so a coating of TiO2 nanoparticles is applied (see Example 4). In an embodiment, the coating includes a first step of exposing the base porous ceramic membrane to a composition comprising TiO2 nanoparticles and a binder. In a second step, the porous ceramic support layer thus coated is dried and sintered to remove the binder and solidify the layer of TiO2 nanoparticles on the porous ceramic support layer, thereby obtaining a porous ceramic support layer coated with TiO2 (see Example 4 and referred to herein as YSZ-TiO2-T). Wherein this coating further reduces the average pore size, as is apparent from the increased area resistance (see Table 4), it has little effect on the ionic conductivity, as shown in Table 4. Figure 5 As can be seen in Figure 2, ionic conductivity is a key parameter in electrochemical applications. In addition to reducing permeability without affecting other electrochemical properties such as conductivity and stability, it has been observed that after further densification of the pores (see below), the TiO2 coating also acts as a barrier to better retain the polymer, and in particular the ionomer. This will inevitably lead to long-term stable performance of the membrane in electrochemical applications.
[0112] Further densification of the pores is accomplished using a polymer. Referring to the examples below, this can be accomplished using suitable techniques such as impregnation or in situ polymerisation.
[0113] In a specific embodiment, densification of the coated ceramic membrane (YSZ-TiO2-T) with an ionomer is accomplished via ionomer impregnation (Example 5) or via in-situ polymerization of the pore walls, the method comprising: (i) grafting the wall with a surface linker, (ii) grafting an initiator molecule onto the surface linker, and (iii) performing SI-ATRP polymerization using various monomers to form the desired polymer layer. The in-situ polymerization of the pore walls may, for example, comprise preparing an alkaline stable monomer, i.e., 1-(4-vinylphenyl)-2-phenyl-1H-benzimidazole, grafting the coated ceramic membrane (YSZ-TiO2-T) with a surface linker, aminopropylphosphonic acid, grafting an initiator molecule, α-bromoisobutyryl bromide, onto the surface linker, and polymerizing with an alkaline stable monomer.
[0114] The overall process is schematically outlined in Figure 6 middle.
[0115] Numbered embodiments of the present invention
[0116] 1. A dense composite polymer-ceramic material comprising:
[0117] a ceramic porous support layer consisting of TiO2 nanoparticles and at least one further metal oxide nanoparticles,
[0118] a porous coating of TiO2 nanoparticles coated on the ceramic porous support layer, and
[0119] • A polymer that fills the pores of both the porous ceramic support layer and the coating.
[0120] 2. A dense composite polymer-ceramic membrane of embodiment 1, wherein at least additional metal oxide nanoparticles are selected from alumina (Al2O3), yttria fully stabilized zirconia (Y2O3-doped ZrO2 (YSZ)), yttria tetragonal zirconia polycrystals (Y2O3-doped ZrO2 (Y-TZP)), CeO2, CeO2 tetragonal ZrO2 polycrystals (Ce-TZP), ZrO2, SiO2, SnO2 and the like; specifically, at least additional metal oxide nanoparticles are yttria-doped zirconia (YSZ).
[0121] 3. The dense composite polymer-ceramic material of embodiment 1 or 2, further comprising a polymer resin, in particular a cross-linkable polymer.
[0122] 4. The dense composite polymer-ceramic material of embodiment 3, wherein the polymer resin is selected from acrylates that can be cross-linked using a thermal initiator (e.g., a cross-linking agent), or acrylates that can be cross-linked using an initiator activated by ultraviolet (UV) light, such as but not limited to polyethylene glycol diacrylate (PEGDA) plus a thermal initiator (e.g., 3 wt. % Luperox 331).
[0123] 5. A dense composite polymer-ceramic material according to any of the preceding embodiments, wherein the ceramic porous support material comprises TiO2 nanoparticles in an amount of about 1 wt% to about 20 wt% of the total dense composite polymer-ceramic material, specifically about 5 wt% to about 15 wt% of the total dense composite polymer-ceramic material.
[0124] 6. A dense composite polymer-ceramic material according to any of the preceding embodiments, wherein the ceramic porous support material comprises at least additional metal oxide nanoparticles of about 50 wt % to about 80 wt %, specifically about 60 wt % to about 70 wt %, of the total ceramic porous support material.
[0125] 7. The dense composite polymer-ceramic material according to any one of the preceding embodiments, wherein the ceramic porous support layer has an average pore size of about 80 to 200 nm.
[0126] 8. The dense composite polymer-ceramic material according to any one of the preceding embodiments, wherein the ceramic porous support material is a membrane having a thickness of about 50 to 2000 μm, specifically 50 to 1000 μm, more specifically 50 to 200 μm.
[0127] 9. The dense composite polymer-ceramic material according to any one of the preceding embodiments, wherein the coating of TiO2 nanoparticles has an average thickness of 0.5 to 5 μm and an average pore size distribution of 50 to 150 nm.
[0128] 10. The dense composite polymer-ceramic material according to any one of embodiments 1 to 9, wherein the polymer filling in the pores of the ceramic porous support material is accomplished via polymer impregnation.
[0129] 11. The dense composite polymer-ceramic material according to embodiment 10, wherein the polymer is selected from any suitable polymer, such as polysulfone (PSU) and polypropylene oxide (PPO), anion binding polymers, ionomers or combinations thereof.
[0130] 12. A dense composite polymer-ceramic material according to embodiment 11, wherein the ionomer is selected from: a halogen ionomer, such as a fluorinated ionomer containing a sulfonate group based on an ionized sulfonic acid (e.g., a fluorosulfonic acid (i.e., FSA) ionomer); or a hydrocarbon ionomer, which preferably contains a (meth)acrylate group based on an ionized (meth)acrylic acid; or a combination thereof.
[0131] 13. The dense composite polymer-ceramic material according to any one of embodiments 1 to 9, wherein filling the pores of the ceramic porous support material with the polymer is accomplished via in situ polymerization of the pore walls.
[0132] 14. A dense composite polymer-ceramic material according to embodiment 12, wherein the in situ polymerization consists of a surface initiated atom transfer radical polymerization (SI-ATRP) reaction; specifically using monomers such as (but not limited to) acrylates and styrene derivatives.
[0133] 15. A method of making a dense composite polymer-ceramic material as defined in any one of embodiments 1 to 13, comprising:
[0134] combining TiO2 nanoparticles, at least another metal oxide nanoparticles, and a curable polymer resin to produce a mixture;
[0135] curing the mixture to obtain a first composite material;
[0136] heating the first composite material to a first temperature to remove the polymer from the first composite material to obtain a second composite material;
[0137] heating the second composite material to a second temperature to sinter the TiO2 nanoparticles and the at least one additional metal oxide nanoparticles, thereby producing a ceramic porous support layer;
[0138] coating the ceramic porous support layer with a TiO2 suspension to obtain a ceramic porous support layer coated with TiO2; and
[0139] Filling the pores of the TiO2 coated ceramic porous support layer with a polymer to obtain a dense composite polymer-ceramic material as defined in any one of embodiments 1 to 14.
[0140] 16. The method of embodiment 15, wherein at least the additional metal oxide nanoparticles are selected from aluminum oxide (Al2O3), yttria fully stabilized zirconia (Y2O3-doped ZrO2 (YSZ)), yttria tetragonal zirconia polycrystalline (Y2O3-doped ZrO2 (Y-TZP)), CeO2, CeO2 tetragonal ZrO2 polycrystalline (Ce-TZP), ZrO2, SiO2, SnO2 and the like; specifically, at least the additional metal oxide nanoparticles are yttria-doped zirconia (YSZ).
[0141] 17. The method of embodiment 15, wherein the polymer resin is selected from acrylates that can be crosslinked using a thermal initiator (e.g., a crosslinker), or acrylates that can be crosslinked using an initiator activated by ultraviolet (UV) light, such as but not limited to polyethylene glycol diacrylate (PEGDA) plus a thermal initiator (e.g., 3 wt % Luperox 331).
[0142] 18. The method of embodiment 15, wherein the mixture comprises about 1 wt % to about 20 wt % of the total mixture of TiO2 nanoparticles, at least additional metal oxide nanoparticles, and the curable polymer resin, specifically about 5 wt % to about 15 wt % of the total mixture of TiO2 nanoparticles.
[0143] 19. The method of embodiment 15, wherein the mixture comprises about 50 wt % to about 80 wt % of the total mixture of TiO2 nanoparticles, at least additional metal oxide nanoparticles, and the curable polymer resin, specifically about 60 wt % to about 70 wt % of the total mixture of at least additional metal oxide nanoparticles.
[0144] 20. The method of embodiment 15, wherein the TiO2 suspension comprises from about 1 wt% to about 5 wt% TiO2.
[0145] 21. The method of embodiment 15, wherein the porous ceramic support material is coated with TiO2 via dip coating.
[0146] 22. The method of any one of embodiments 15 to 21, wherein pore filling of the layer of polymer brushes formed is performed via in situ polymerization of the pore walls to further functionalize the porous ceramic support material coated with TiO2.
[0147] 23. The method of embodiment 22, wherein the in situ polymerization consists of a surface initiated atom transfer radical polymerization (SI-ATRP) reaction; in particular using monomers such as (but not limited to) acrylates and styrene derivatives.
[0148] 24. The method of any one of embodiments 15 to 21, wherein the pores of the TiO2 coated porous ceramic support material are filled with the polymer via polymer impregnation.
[0149] 25. The method of embodiment 24, wherein the polymer is selected from any suitable polymer, such as polysulfone (PSU) and polypropylene oxide (PPO), anion binding polymers, ionomers, or combinations thereof.
[0150] 26. The method of embodiment 25, wherein the ionomer is selected from: a halogen ionomer, such as a fluorinated ionomer containing sulfonate groups based on ionized sulfonic acid (e.g., a fluorosulfonic acid (i.e., FSA) ionomer); or a hydrocarbon ionomer, which preferably contains (meth)acrylate groups based on ionized (meth)acrylic acid; or a combination thereof.
[0151] 27. The method according to any one of embodiments 24 to 26, wherein:
[0152] Filling the pores of one side of a ceramic porous support layer coated with TiO2 with a first ionomer via diffusion of a solution of the ionomer from that side followed by precipitation of the ionomer, and
[0153] • Filling the pores of the other side of the TiO2 coated ceramic porous support layer with a second ionomer via diffusion of a solution of the ionomer from the second side followed by precipitation of the ionomer.
[0154] 28. Use of the dense composite polymer-ceramic material according to any one of embodiments 1 to 14 or the dense composite polymer-ceramic material obtained by the method according to any one of embodiments 15 to 27 in filtration or electrochemical applications, such as fuel cells, hydrogen peroxide production and alkaline water electrolysis. Example
[0155] Example 1. Preparation of Inorganic Particle-Polymer Slurry
[0156] In the thinky mixer (ARE-250CE) slurry container, 5.4 g of polyethylene glycol diacrylate (PEGDA, 27 wt%, Sigma-Aldrich, average M n575), followed by 6 g of YSZ (TOSOH EUROPE BV). They were mixed at 2000 rpm for 2 min. The remaining YSZ (6 g) was added and mixed at 2000 rpm for 2 min. Similarly, 10 wt % TiO2 nanoparticles (2 g) were added and mixed at 2000 rpm for 2 min. The slurry container was cooled to room temperature before proceeding to the next step. Finally, 3 wt % of L331 initiator (Arkema) (0.67 mL) relative to the total mixture was added and mixed at 2000 rpm for 2 min, followed by a defoaming step and mixing at 900 rpm for 1 min. In parallel, a slurry without TiO2 nanoparticles and with 70 wt % YSZ was prepared for comparison of YSZ-based film properties with and without TiO2.
[0157] Example 2. Preparation of membrane green body
[0158] Prepared with different sizes (such as 3cm, 5cm diameter and 5.3×3.3cm 2 A Teflon mold (500 μm) of rectangular shape was placed on top of a glass support. The uniform slurry was filled in a syringe container and pressed and poured into the Teflon mold placed on top of the glass support. Then, using a second glass cover, the slurry was pressed and evenly distributed to fill the chamber. Four clamps were used to clamp at the ends of the glass cover and the support. Then, a laboratory shaker was used to shake the sample at 85 times per minute for 2 hours. Then, it was thermally cured overnight in an oven at 100°C. The self-supporting polymer / nanoparticle material (called a film green body) was collected from the mold.
[0159] Example 3. Preparation of porous ceramic membrane
[0160] Briefly, the polymer template was removed from the membrane green body by heating the sample in a box furnace under air at 180°C for 2 h, 250°C for 4 h, and 400°C for 2 h. A heating rate of 60°C / h was used. Subsequently, the ceramic nanoparticles were heated from 400°C to 800°C at a heating rate of 120°C / h and maintained for a residence time of 4 h. Then, the temperature was increased to 1100°C for 15 h and decreased to 80°C at a heating and cooling rate of 120°C / h. In this way, the porous ceramic membranes prepared with and without TiO2 nanoparticles were named YSZ-TiO2 and YSZ, respectively. Table 1 presents the composition of the porous ceramic membranes.
[0161] Composition of prepared porous ceramic membrane
[0162] Table 1. Film composition (nanoparticles, polymer binder and initiator)
[0163]
[0164] *Weight % is calculated taking into account the total weight of the slurry.
[0165] Example 4. Preparation of TiO2 suspension and coating of YSZ-TiO2 film to produce YSZ-TiO2-T film
[0166] Commercially available TiO2 powder (about 100nm size, rutile phase, 99.9%, USResearch Nanomaterials Inc, USA) and polyvinyl alcohol (PVA 72000, Fluka Chemica) were used as starting powder and binder to make TiO2 suspension. A certain amount of TiO2 powder particles were dispersed in DI water and ultrasonically treated for 15min. Table 2 presents the composition of the prepared TiO2 suspension. Then, the obtained suspension was stirred for 2h. After that, 1 wt% of PVA was added to the suspension as a binder. Then, the suspension was continuously stirred for 24h and then degassed in a vacuum environment to remove air bubbles.
[0167] Table 2. Composition of the prepared TiO2 suspension
[0168] <![CDATA[TiO2 (wt%)]]> PVA (wt%) DI water (wt%) 3 1 96
[0169] The prepared TiO2 suspension was coated on the surface of the prepared ceramic membrane using dip coating (RDS15 dip coater) with 30 s dip time and 5 mm / s pull speed. The modified membrane was then dried at room temperature for 48 h. After that, the membrane was heated to 500 °C for 3 h to remove the PVA binder and then continuously heated to 800 °C for 4 h under air to reach the sintering temperature. The heating and cooling rates were each set to 1 °C / min.
[0170] Example 5. Densification of membranes via ionomer impregnation to produce YSZ-TiO2-T ionomer membranes
[0171] The impregnation of commercially available ionomers into pristine or modified porous ceramic membranes was accomplished by: impregnating AP2-HNN8-00-X (Aemion+ TM , high ion exchange capacity anion exchange polymer dry resin) was dissolved in NMP or methanol (5 to 20 wt. / v%). The ceramic membrane was immersed in the prepared solution for 24 h. The membrane was taken out and the surface was cleaned using a paper towel moistened with NMP or methanol to remove the surface polymer resin. Then, the membrane was immersed in DI water for 24 h. Then, the membrane was dried in a 50°C oven for 24 h before further characterization.
[0172] Example 6: Membrane Characterization
[0173] The following characterizations were performed on both modified and unmodified membranes.
[0174] The thickness and diameter of the prepared porous ceramic membrane were characterized before and after sintering. The ionic conductivity, density, porosity, pore size and thermal stability of the final porous ceramic membrane were characterized.
[0175] The performance of the prepared porous ceramic membranes was also tested in alkaline water electrolysis using the following conditions.
[0176] parameter Value / Type Catholyte 1M KOH Anolyte 1M KOH Current Collector Optimized board temperature 25, 40 and 60°C Scan speed 10mV / s Room pressure 4 bar flow 200ml / min
[0177] Figure 2 The percentage weight of polymer removed from different batches of membranes after sintering is shown. For this, the weight of the membrane before and after sintering is recorded. The reduction indicates successful removal of polymer from the material and its amount, shown to be consistent in different batches.
[0178] Table 3. Physical properties of the prepared membranes (pore size, pore size distribution and porosity) determined via Hg porosimetry. The bulk density and apparent density of the membranes were determined via He pycnometer.
[0179] unit <![CDATA[YSZ-TiO2]]> <![CDATA[YSZ-TiO2-T]]> Total hole area <![CDATA[m 2 / g]]> 3.9 3.6 Total cumulative volume <![CDATA[mm 3 / g]]> 244 239 Average pore size nm 172 169 Bulk density <![CDATA[g / cm 3 ]]> 2.6 2.5 Apparent density <![CDATA[g / cm 3 ]]> 7.1 6.0 Porosity % 63 59 thickness μm 600-700 600-700
[0180] Figure 3 The pore size distribution of the YSZ-TiO2 membrane is shown. The YSZ-TiO2 membrane exhibits a surprisingly narrow pore size distribution with an average pore size of 172 nm. The values range from about 90 nm to about 200 nm. The cumulative pore volume is up to about 240 mm 3 / g.
[0181] Table 4. Ionic conductivity of YSZ-TiO2, YSZ-TiO2-T and YSZ-TiO2-T-ionomer membranes
[0182]
[0183] The ionic conductivity of 6M KOH at 30°C is 688 mS / cm.
[0184] Alkaline stability of the prepared membranes in 6 M KOH at 60 °C for 14 days
[0185] membrane Weight loss (%) Ionic conductivity loss <![CDATA[YSZ-TiO2]]> ND ND <![CDATA[YSZ-TiO2-T]]> ND ND <![CDATA[YSZ-TiO2-T-Ionomer]]> ND ND
[0186] ND: Not Detected. The membrane is stable under these conditions.
[0187] Gas Permeability of YSZ-TiO2, YSZ-TiO2-T and YSZ-TiO2-T-ionomer Membranes
[0188] membrane <![CDATA[Gas flow rate at 5 bar (L / min.cm 2 )]]> <![CDATA[YSZ-TiO2]]> 4.28+0.87 <![CDATA[YSZ-TiO2-T]]> 3.95+0.38 <![CDATA[YSZ-TiO2-T-Ionomer]]> 2.20+0.24
[0189] Figure 4Thermogravimetric analysis (TGA) of PEGDA (lower line), curing (middle line) and sintering (upper line) of YSZ-TiO2 films are shown. The sintered material is stable over the tested temperature range.
[0190] Figure 5 Preliminary alkaline water electrolysis using membranes according to the present invention is presented and shows a consistent correlation between potential (V) and current density for porous ceramic membranes (YSZ-TiO2) and porous ceramic membranes coated with TiO2 (YSZ-TiO2-T).
Claims
1. A dense composite polymer-ceramic material consisting of: a ceramic porous support layer consisting of TiO2 nanoparticles and at least one further metal oxide nanoparticles, a porous coating of TiO2 nanoparticles coated on the ceramic porous support layer, and • A polymer that fills the pores of the ceramic porous support layer and the porous coating of the TiO2 nanoparticles.
2. A dense composite polymer-ceramic membrane according to claim 1, wherein the at least additional metal oxide nanoparticles are selected from alumina (Al2O3), yttria fully stabilized zirconia (Y2O3-doped ZrO2 (YSZ)), yttria tetragonal zirconia polycrystalline (Y2O3-doped ZrO2 (Y-TZP)), CeO2, CeO2 tetragonal ZrO2 polycrystalline (Ce-TZP), ZrO2, SiO2, SnO2 and the like; specifically, the at least additional metal oxide nanoparticles are yttria-doped zirconia (YSZ).
3. The dense composite polymer-ceramic material according to any of the preceding claims, wherein the ceramic porous support layer comprises about 1 wt % to about 20 wt % of the ceramic porous support layer, in particular about 5 wt % to about 15 wt % of the ceramic porous support layer of TiO2 nanoparticles.
4. The dense composite polymer-ceramic material according to any of the preceding claims, wherein the ceramic porous support layer comprises about 50% to about 80% by weight of the ceramic porous support layer, in particular about 60% to about 70% by weight of the ceramic porous support layer of the at least additional metal oxide nanoparticles.
5. The dense composite polymer-ceramic according to any one of the preceding claims, wherein the ceramic porous support layer has an average pore size of about 80 to 200 nm.
6. The dense composite polymer-ceramic material according to any one of the preceding claims, wherein the dense composite polymer-ceramic material is a film having a thickness of about 50 to 2000 μm, specifically 50 to 1000 μm, more specifically 50 to 200 μm.
7. The dense composite polymer-ceramic material according to any one of the preceding claims, wherein the porous coating of TiO2 nanoparticles has an average thickness of 0.5 to 5 μm and an average pore size distribution of 50 to 150 nm.
8. The dense composite polymer-ceramic material according to any one of claims 1 to 7, wherein filling the pores with polymer is accomplished via polymer impregnation.
9. The dense composite polymer-ceramic material according to claim 8, wherein the polymer is selected from any suitable polymer such as polysulfone (PSU) and polypropylene oxide (PPO), ion exchange polymers, ionomers or combinations thereof.
10. A dense composite polymer-ceramic material according to claim 9, wherein the ionomer is selected from: a halogen ionomer, such as a fluorinated ionomer containing sulfonate groups based on ionized sulfonic acid (e.g., fluorosulfonic acid (FSA)) ionomer); an anion-containing ionomer (such as an ionomer containing tetrasubstituted amine groups); or a hydrocarbon ionomer, which preferably contains (meth)acrylate groups based on ionized (meth)acrylic acid; or a combination thereof.
11. A method of making a dense composite polymer-ceramic material as defined in any one of claims 1 to 10, comprising: combining TiO2 nanoparticles, at least another metal oxide nanoparticles, and a curable polymer resin to produce a mixture; curing the mixture to obtain a first composite material; heating the first composite material to a first temperature to remove polymer from the first composite material to obtain a second composite material; heating the second composite material to a second temperature to sinter the TiO2 nanoparticles and the at least one additional metal oxide nanoparticles, thereby producing a ceramic porous support layer; coating the ceramic porous support layer with a TiO2 suspension to obtain a ceramic porous support layer coated with TiO2; and Filling the pores of the TiO2 coated ceramic porous support layer with a polymer to obtain a dense composite polymer-ceramic material as defined in any one of claims 1 to 10.
12. The method of claim 11, wherein the at least additional metal oxide nanoparticles are selected from alumina (Al2O3), yttria fully stabilized zirconia (Y2O3-doped ZrO2 (YSZ)), yttria tetragonal zirconia polycrystalline (Y2O3-doped ZrO2 (Y-TZP)), CeO2, CeO2 tetragonal ZrO2 polycrystalline (Ce-TZP), ZrO2, SiO2, SnO2 and the like; specifically, the at least additional metal oxide nanoparticles are yttria-doped zirconia (YSZ).
13. The method of claim 11, wherein the polymer resin is selected from acrylates that can be crosslinked using a thermal initiator (e.g., a crosslinker), or acrylates that can be crosslinked using an ultraviolet (UV) light activated initiator, such as but not limited to polyethylene glycol diacrylate (PEGDA) plus a thermal initiator (e.g., 3 wt. % Luperox 331).
14. The method of claim 11, wherein the mixture comprises about 1 wt % to about 20 wt % of the total mixture of TiO2 nanoparticles, at least additional metal oxide nanoparticles, and a curable polymer resin, specifically about 5 wt % to about 15 wt % of the total mixture of TiO2 nanoparticles.
15. The method of claim 11, wherein the mixture comprises about 50 wt % to about 80 wt % of the total mixture of TiO2 nanoparticles, at least additional metal oxide nanoparticles, and a curable polymer resin, specifically about 60 wt % to about 70 wt % of the total mixture of at least additional metal oxide nanoparticles.
16. The method of claim 11, wherein the TiO2 suspension comprises about 1 wt% to about 5 wt% TiO2.
17. A method according to any one of claims 11 to 16, wherein: Filling the pores of one side of the TiO2-coated ceramic porous support layer with a first ionomer via diffusion of a solution of the ionomer from that side followed by precipitation of the ionomer, and • Filling the pores of the other side of the TiO2 coated ceramic porous support layer with a second ionomer via diffusion of a solution of the ionomer from the second side followed by precipitation of the ionomer.
18. Use of the dense composite polymer-ceramic material according to any one of claims 1 to 10 or obtained by the method according to any one of claims 11 to 17 in filtration or electrochemical applications, such as fuel cells, hydrogen peroxide production and alkaline water electrolysis.
Citation Information
Patent Citations
Porous ceramic structure for carbon dioxide capture
US20190389778A1
Ceramic nanofiltration membrane with polymers grafted into the pores and method of producing same
WO2020016068A1